2002
DOI: 10.1074/jbc.m108600200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-ζ Regulates Transcription of the Matrix Metalloproteinase-9 Gene Induced by IL-1 and TNF-α in Glioma Cells via NF-κB

Abstract: The regulation of matrix metalloproteinase-9 (MMP-9) expression in glioma cells is one of the key processes in tumor invasion through the brain extracellular matrix. Although some studies have demonstrated the implication of classic protein kinase C (PKC) isoforms in the regulation of MMP-9 production by phorbol esters or lipopolysaccharide, the involvement of specific PKC isoforms in the signaling pathways leading to MMP-9 expression by inflammatory cytokines remains unclear. Here we report that the atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
124
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(137 citation statements)
references
References 40 publications
13
124
0
Order By: Relevance
“…We also show that diosgenin suppressed TNF-induced invasion by tumor cells, and this inhibition correlated with the downregulation of MMP-9 and COX-2. The role of MMP-9 and COX-2 in invasion has been demonstrated earlier (Yamamoto et al, 1995;Attiga et al, 2000;Esteve et al, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…We also show that diosgenin suppressed TNF-induced invasion by tumor cells, and this inhibition correlated with the downregulation of MMP-9 and COX-2. The role of MMP-9 and COX-2 in invasion has been demonstrated earlier (Yamamoto et al, 1995;Attiga et al, 2000;Esteve et al, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…The gene products that have been linked with invasion and angiogenesis [matrix metalloproteinase-9 (MMP-9) and vascular endothelial growth factor (VEGF)] are regulated by NF-nB (52,53). We determined whether the expression of these gene products is modulated by TQ.…”
Section: Tq Suppresses Tnf-induced Nf-jb -Dependent Gene Products Invmentioning
confidence: 99%
“…It enhances cytokines, chemokines, and angiogenic factor expression which promotesneovascularization to support tumor growth (Nabors et al, 2003;Kulbe et al, 2007). TNF increases the invasiveness of tumor cells by inducing expression of matrix metalloproteinase (MMP) (Esteve et al, 2002;Cheng et al, 2007). In a study with a coculture model between macrophages and tumor cells demonstrated that TNF-α secreted by macrophages promotes invasiveness of tumour cells by induction of matrix metalloproteinase (Pollard 2004).…”
Section: Discussionmentioning
confidence: 99%